Bacillus subtilis MazF-bs (EndoA) is a UACAU-specific mRNA interferase - Park, Jung-Ho (2011)
MazF is an mRNA interferase which cleaves mRNAs at a specific sequence. Here, we show that in contrast to MazF-ec from Escherichia coli, which specifically cleaves ACA sequences, MazF-bs from Bacillus subtilis is an mRNA interferase that specifically cleaves a five-base sequence, UACAU. MazF homologues widely prevailing in Gram-positive bacteria were found to be highly homologous to MazF-bs, suggesting that they may also have similar cleavage specificity. This cleavage site is over-represented in the B. subtilis genes associated with biosynthesis of secondary metabolites, suggesting that MazF-bs may be involved in the regulation of the production of secondary metabolites.